Management Solutions for Better Business Performance based on a Six Factor Model on VMD Stock Price – A Case in Medicine Industry in Vietnam - THUY, DO MINH; HUY, DINH TRAN NGOC; THUY, NGUYEN THU (The journal of contemporary issues in business and government, 2021)
What are macro effects on business performance indicators such as stock price in medicine sector and such firms such as Vimedimex (VMD) in Vietnam? Is it the time we propose better management model via analyzing business performance under macro factors effects? This paper will use quantitative and qualitative analytical methods, such as synthesis and inductive, with OLS regression supported by Eviews. First, we found that many macro factors have negative correlation with stock price of firm, VMD. Whereas Risk free rate (Rf) has positive correlation with stock price. Next we discovered better business performance will be affected by better stock price management. Hence, management team need to predict effects from macro policies on their stock price as our suggested model. We believe these findings could be used by companies and investors as a prediction of stock price management.